Implementation of Cognitive Theory Learning in Increasing the Interest in Learning Mathematics of Grade 5 Students of State Elementary School 2 Tukadsumaga - Elya Trisnayanti, Ni Putu; Suarni, Ni Ketut; Margunayasa, I Gede (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This research raises issues surrounding students' difficulties in concentrating, especially in learning mathematics which is often considered difficult. The objectives of this research include: 1) evaluating the impact of applying cognitive learning theory on increasing students' interest in learning in mathematics, 2) identifying ways to implement cognitive theory to increase interest in learning mathematics, and 3) analyzing the strengths and weaknesses in applying cognitive learning theory. This research uses a qualitative approach by collecting data through documentation and interviews. The research subjects involved one teacher as homeroom teacher and sixteen fifth grade students at SD Negeri 2 Tukadsumaga. The research results show that the implementation of cognitive learning theory has a positive impact in increasing students' interest in learning, especially in learning mathematics. Students' enthusiasm and activeness during the learning process reflects the effectiveness of applying this theory, with students actively taking notes and asking questions to the teacher and being able to understand the lesson material. In conclusion, cognitive learning theory has great potential in increasing students' learning interest in mathematics subjects. Penelitian ini mengangkat permasalahan seputar kesulitan siswa dalam berkonsentrasi, terutama dalam pembelajaran matematika yang sering dianggap sulit. Penelitian ini bertujuan untuk: 1) mengevaluasi pengaruh teori belajar kognitif terhadap peningkatan minat belajar siswa pada mata pelajaran matematika, 2) mengidentifikasi strategi implementasi teori kognitif yang digunakan untuk meningkatkan minat belajar matematika, dan 3) menganalisis kelebihan dan kelemahan dalam menerapkan teori belajar kognitif. Pendekatan kualitatif digunakan dengan mengumpulkan data melalui dokumentasi dan wawancara. Subjek penelitian melibatkan satu guru sebagai wali kelas dan enam belas siswa kelas V di SD Negeri 2 Tukadsumaga. Temuan penelitian menunjukkan bahwa penerapan teori belajar kognitif berdampak positif dalam meningkatkan minat belajar siswa, terutama dalam konteks pembelajaran matematika.. Semangat dan keaktifan siswa selama proses pembelajaran mencerminkan efektivitas penerapan teori ini, dengan siswa secara aktif mencatat dan bertanya kepada guru, serta mampu memahami materi pelajaran. Kesimpulannya, teori belajar kognitif memiliki potensi besar dalam meningkatkan minat belajar siswa pada mata pelajaran matematika.